Music Therapist Experiences of a Randomized Controlled Trial as Clinician Researchers. (30th March 2020) - Henley, Amanda K; Collier, Elizabeth; Robertson, Kim; Biard, Marial A; Bruno, Kathryn; Bush, Hannah; Frees, Erinn; Krater, Caitlin; Woolever, Sarah; Burns, Debra S; Robb, Sheri L
Abstract: Music therapy clinicians bring an important perspective to the design and conduct of clinically meaningful studies. Unfortunately, there continue to be roadblocks that hinder clinician involvement in research and the development of successful partnerships between academic researchers and practicing clinicians. To help grow clinician involvement, it is important that research teams share their experiences. As such, the purpose of this qualitative study was to share music therapists' perspectives about their experience of working as a research clinician on a large multisite randomized controlled trial. 10 board-certified music therapists provided written responses to 6 data-generating questions about: (a) reasons for participating, (b) perceived challenges and benefits, (c) experiences of quality assurance monitoring, (d) professional growth, (e) value of research, and (f) advice for clinicians considering research involvement. Using thematic content analysis, we identified primary themes and subthemes for each question (20 themes; 30 subthemes). Qualitative analysis revealed not only common challenges, such as reconciling clinical and research responsibilities, but also benefits, including continued professional growth, greater understanding of research processes, and research participation as a way to advocate and advance the profession. Finally, for clinicians interested in becoming involved in research, therapists noted the importance of having workplace support from a mentor, supervisor, and/or administrator; seeking out available resources; and knowing roles and responsibilities before initiating research involvement. Findings offer important insight and recommendations to support the involvement of clinicians in research and support further exploration of clinician involvement in dissemination efforts to improve translation and uptake of research into practice.